Seasonal variations of reproductive parameters, semen quality and testosterone levels of Highlander rams - Ojeda Fermoselle, Pablo M. (2021)
The aim of this work was to determine the effect of the season of the year (photoperiod) on scrotal circumference (SC), testicular weight (TW), testicular volume (TV), serving capacity test (SCT), plasma testosterone concentration and semen quality traits in Highlander rams. The study was carried out in the humid pampas of Argentina (130 m above sea level) with six adult rams (5-6 years old). Monthly determinations of body weight, body condition score, SC, TW [TW = 0.5533 x (L) x (W)2], TV [TV=4/3 x (π) x (L/2) x (W/2)2], being L=long and W=width of the testicle, and plasma testosterone. The SCT was performed twice per season and the semen evaluation twice per week during the central month of each season. The analysis was done using linear mixed models for repeated measures (R Core Team). In summer (March) the highest values of SC (mean ± SE; p<0.05) (34.2 ± 0.7 cm), TW (506.7 ± 21.2 g) and TV (479.7 ± 20.0 cm3) were observed. The average number of total mounts was higher (p<0.05) in winter (15) compared to spring (10) and summer (8.5). The highest plasma testosterone concentration (p<0.05) was observed in summer (January = 15.2 ± 4.3 ng/ml) and the lowest in winter (August = 0.12 ± 0.1 ng/ml). In ejaculates (n=192), a lower volume was observed in spring and summer (p<0.05). Total sperm motility (%), vigor and sperm concentration registered a significant decrease (p<0.05) in summer. No significant differences were observed in the percentages of individual progressive motility and normal sperm between seasons. The results suggest that Highlander rams have a higher reproductive potential during autumn (decreasing photoperiod).